INSTALASI KINETIK PADA SET PANGGUNG LAKON SUDDENLY LAST SUMMER KARYA TENNESSEE WILLIAMS DENGAN PENDEKATAN REALISME SUGESTIF - Nugroho, Eko Bambang Wisnu; Iskandar, Andang; Safitri, Riana (Jurusan Seni Rupa ISBI Bandung, 2021)
The kinetic installation of the stage set will use a suggestive realism approach. This installation reinforces the existing symbols and does not embody all the elements in the play. The visualization of the work carried out in the first stage is to analyze the script and the matrix design of the realist play Suddenly Last Summer. The second stage, the kinetic installation sketch of the stage set is realized in the form of working drawings. The third stage the designer implements the kinetic installation design concept of the stage set and it is realized. In the final stage, all the stage set kinetic installation designs are assembled and then simulated. The concept of this installation is the interpretation of the analysis of the series of events in Tennessee Williams's play Suddenly Last Summer which is realized in a post-minimalist style through a suggestive realism approach. The process of making this work is still in a state of the COVID-19 pandemic. Therefore, the show was replaced through a simulation in the form of 3D animated videos, mockups, examples of kinetic installation models (dummy) on stage sets, and several other supporting elements.Keywords: Kinetic installation, Suddenly Last Summer, Tennessee William, suggestive realism——————————————————————————————Instalasi kinetik set panggung lakon ini akan memakai pendekatan realisme sugestif. Instalasi ini lebih menguatkan simbol-simbol yang ada dan tidak mewujudkan keseluruhan elemen-elemen di dalam lakon tersebut. Visualisasi karya yang dilakukan pada tahap pertama yaitu membuat analisa naskah dan matriks rancangan lakon realis Suddenly Last Summer. Tahap kedua, sketsa instalasi kinetik set panggung tersebut diwujudkan ke dalam bentuk gambar kerja. Tahap ketiga perancang mengimplementasikan konsep rancangan instalasi kinetik set panggung dan direalisasikan. Tahap akhir semua rancangan instalasi kinetik set panggung dirangkai untuk kemudian disimulasikan. Konsep instalasi ini merupakan hasil interpretasi dari analisa rangkaian peristiwa lakon Suddenly Last Summer karya Tennessee Williams yang diwujudkan dengan gaya post-minimalist melalui pendekatan realisme sugestif. Proses penggarapan karya ini masih dalam keadaan pandemi COVID-19. Oleh karena itu, pertunjukan digantikan melalui bentuk simulasi dalam bentuk video animasi 3D, maket, contoh model (dummy) instalasi kinetik set panggung, dan beberapa elemen pendukung lainnya.Kata Kunci: Instalasi kinetic, lakon Suddenly Last Summer, Tennessee William, realisme sugestif